(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Studies were carried out on the lipid classes and fatty acid compositions of petuli seed oil. It was observed that petuli seed grown under the soil and climatic condition of Bangladesh contains about 22% pale yellow coloured oil. The total lipids were fractionated into three major lipid classes, neutral lipid glyco lipid and phospho lipid by silicic acid column chromatography. The neutral lipid was accounted to 92.5% of the total weight of the lipid applied. The oil was also fractionated into mono, di and triglyceride by silicic acid column chromatography. The triglyceride was counted for over 90% of the total weight of the oil. The fatty acid compositions of the oil were analyzed by Gas liquid Chromatography and found the major fatty acid ?-elaeostearic acid 38.50%, oleic acid 34.35%, linoleic acid 26.15% and small amount of arachidic acid 1%. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10716 Bangladesh J. Sci. Ind. Res. 47(1), 105-108, 2012